Identification of a effective cooperation model in the game positioning in a volleyball game - Leszek Mazur (Nicolaus Copernicus University in Toruń, 2017)
Streszczenie Praca ma na celu identyfikację modelu odwzorowującego efektywne współdziałanie w pozycjonowaniu gry  (przyjęciu zagrywki - podaniu) w piłce siatkowej. W pracy wykorzystano oryginalną metodę badawczą zwaną pragmatycznym studium unikatowych przypadków. Badania obejmują obserwację zespołu narodowego Stanów Zjednoczonych w grze podczas Igrzysk Olimpijskich w Rio de Janeiro 2016. Na podstawie obserwacji oraz wykorzystania autorskiego arkusza obserwacji przyjęcia zagrywki udało się zidentyfikować pewien model odwzorowujący efektywne współdziałanie w przyjęciu-podaniu zagrywki, oparty o kryterium dokładności współdziałania oraz elastyczności współdziałania. Na podstawie badań można też stwierdzić, że istnieją różne modele współdziałania w tym elemencie, które stosują drużyny o największej efektywności sportowej. Modele te różnią się od siebie. Praca ta skłania do przemyśleń na temat identyfikowania współdziałania w grach zespołowych i zachęca do prowadzenia dalszych badań w tym temacie.  Abstract Purpose: The paper is aimed at identification of a model which shows the effective cooperation in the game positioning (exactly in receiving-passing the ball) in a volleyball game. Design/methodology/approach: The original research method is used in this thesis which is called pragmatic unique case study. The research is aimed at observation USA team playing volleyball during The Olympic Games in Rio de Janeiro 2016.  Findings: There is a cooperation model in receiving and passing the ball among USA volleyball team players found, based on the observation. There are also other cooperation models used by teams.                    Research and practical limitations/implications: Based in the research I can tell that there are different models of cooperation in the game positioning in volleyball. The teams which are the most effective use different models of cooperation while playing.              Originality/value: The paper is original and leads to think about the identification of the process of cooperation in team games. More research in this field is recommended.